Cdc42p GTPase Regulates the Budded-to-Hyphal-Form Transition and Expression of Hypha-Specific Transcripts in Candida albicans - vandenBerg, Alysia L. (American Society for Microbiology, 2004)
The yeast Candida albicans is a major opportunistic pathogen of immunocompromised individuals. It can grow in several distinct morphological states, including budded and hyphal forms, and the ability to make the dynamic transition between these forms is strongly correlated with virulence. Recent studies implicating the Cdc42p GTPase in hypha formation relied on cdc42 mutations that affected the mitotic functions of the protein, thereby precluding any substantive conclusions about the specific role of Cdc42p in the budded-to-hypha-form transition and virulence. Therefore, we took advantage of several Saccharomyces cerevisiae cdc42 mutants that separated Cdc42p's mitotic functions away from its role in filamentous growth. The homologous cdc42-S26I, cdc42-E100G, and cdc42-S158T mutations in C. albicans Cdc42p caused a dramatic defect in the budded-to-hypha-form transition in response to various hypha-inducing signals without affecting normal budded growth, strongly supporting the conclusion that Cdc42p has an integral function in orchestrating the morphological transition in C. albicans. In addition, the cdc42-S26I and cdc42-E100G mutants demonstrated a reduced ability to damage endothelial cells, a process that is strongly correlated to virulence. The three mutants also had reduced expression of several hypha-specific genes, including those under the regulation of the Efg1p transcription factor. These data indicate that Cdc42p-dependent signaling pathways regulate the budded-to-hypha-form transition and the expression of hypha-specific genes.